Developing Character Students Trough Spot Capturing Method in Science Education Learning - Septaria, Kiki (Program Studi Pendidikan IPA, Universitas Islam Lamongan, 2019)
Characters is something that shows how good someone is. Every human being has the characters since they birth. Characters can be developed on a macro or micro basis, one of which is micro ways with learning and teaching activity in schools. Selection method of learning is vey important to develop good character in students. One method student-centered learning is the Spot Capturing method. This research method uses a literature study method that wants to know the characters that can be developed using the Spot capturing method. The literature results show that spot capturing methods can develop several characters in their implementation such as curiosity, honesty, discipline, hard work, creative, responsibility, social care and communicative.